2016
DOI: 10.12968/bjon.2016.25.12.681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the objective structured long examination record for nurse education

Abstract: An objective structured long examination record (OSLER) is a modification of the long-case clinical examination and is mainly used in medical education. This study aims to obtain nursing students' views of the OSLER compared with the objective structured clinical examination (OSCE), which is used to assess discrete clinical skills. A sample of third-year undergraduate nursing students (n=21) volunteered to participate from a cohort of 230 students. Participants undertook the OSLER under examination conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…11 A comparative study of developmental assessment in medicine using traditional long-case examination and objectively structured long examination record (OSLER) for final-year MBBS students also showed that the OSLER warrants a more universal evaluation of a student's clinical skills principally vital skills like communication. 12,13 Pandya et al 14 also concluded in their study that the structured clinical examination technique fulfills almost all features for a perfect clinical proficiency judgment without conceding objectivity, rationality, and reliability and can be used as an assessment tool in clinical assessments. As a fundamental part of medical education, the importance of clinical training is acknowledged by all educational planners and assessing undergraduate students on performance is always challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A comparative study of developmental assessment in medicine using traditional long-case examination and objectively structured long examination record (OSLER) for final-year MBBS students also showed that the OSLER warrants a more universal evaluation of a student's clinical skills principally vital skills like communication. 12,13 Pandya et al 14 also concluded in their study that the structured clinical examination technique fulfills almost all features for a perfect clinical proficiency judgment without conceding objectivity, rationality, and reliability and can be used as an assessment tool in clinical assessments. As a fundamental part of medical education, the importance of clinical training is acknowledged by all educational planners and assessing undergraduate students on performance is always challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Medical teachers always search for the new method that aligns the training during their professional work as physicians. 13,14 Taking this point into consideration, we redesigned our assessment method and tried to cover all domains of learning, including cognition, psychomotor, and attitude. Students are the principal stakeholders in assessment; their point of view is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunity of soft skills that can be measured in the particular procedure were mainly focused on the students and graduate nurses's clinical performance [6], [16], [17]. They have used those developed tools in the OSCE to assess students' clinical competencies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, having more time in the active station with the actors allows students time to move through the Model and Process for Nutrition and Dietetic Practice (MPNDP), as they would in a real clinical situation, rather than focusing on one discrete aspect of the consultation. In addition, integration of skills better reflects the growing competency and skill development of a final‐year student and allows better assessment of communication and clinical reasoning skills . Examiners test clinical reasoning skills further at the end of the active station by asking a standard question.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, integration of skills better reflects the growing competency and skill development of a final-year student 16 and allows better assessment of communication and clinical reasoning skills. 17,18 Examiners test clinical reasoning skills further at the end of the active station by asking a standard question.…”
Section: Introductionmentioning
confidence: 99%